High‐throughput sequencing for biology and medicine - Soon, Wendy Weijia; Hariharan, Manoj; Snyder, Michael P (Molecular systems biology, 2013)
Advances in genome sequencing have progressed at a rapid pace, with increased throughput accompanied by plunging costs. But these advances go far beyond faster and cheaper. High‐throughput sequencing technologies are now routinely being applied to a wide range of important topics in biology and medicine, often allowing researchers to address important biological questions that were not possible before. In this review, we discuss these innovative new approaches—including ever finer analyses of transcriptome dynamics, genome structure and genomic variation—and provide an overview of the new insights into complex biological systems catalyzed by these technologies. We also assess the impact of genotyping, genome sequencing and personal omics profiling on medical applications, including diagnosis and disease monitoring. Finally, we review recent developments in single‐cell sequencing, and conclude with a discussion of possible future advances and obstacles for sequencing in biology and health. Genome sequencing technologies have advanced rapidly, dramatically decreasing cost and increasing throughput. But beyond faster and cheaper, these advances have also stimulated the development of innovative new experimental approaches, and are opening new doors in human medicine and health.